Alteration of β-Adrenoceptor Signaling in Left Ventricle of Acute Phase Takotsubo Syndrome: a Human Study - Nakano, Tomoya; Onoue, Kenji; Nakada, Yasuki; Nakagawa, Hitoshi; Kumazawa, Takuya; Ueda, Tomoya; Nishida, Taku; Soeda, Tsunenari; Okayama, Satoshi; Watanabe, Makoto; Kawata, Hiroyuki; Kawakami, Rika; et al. (Scientific reports, 2018)
Accumulating evidence indicates alteration of the β-adrenoceptor (AR), such as desensitization and subtype switching of its coupling G protein, plays a role in the protection against catecholamine toxicity in heart failure. However, in human takotsubo syndrome (TTS), which is associated with a surge of circulating catecholamine in the acute phase, there is no histologic evidence of β-AR alteration. The purpose of this study was to investigate the involvement of alteration of β-AR signaling in the mechanism of TTS development. Left ventricular (LV) biopsied samples from 26 patients with TTS, 19 with normal LV function, and 26 with dilated cardiomyopathy (DCM) were studied. G protein-coupled receptor kinase 2 (GRK2) and β-arrestin2, which initiate the alteration of β-AR signaling, were more abundantly expressed in the myocardium in acute-phase TTS than in those of DCM and normal control as indicated by immunohistochemistry. The percentage of cardiomyocytes that showed positive membrane staining for GRK2 and β-arrestin2 was also significantly higher in acute-phase TTS. Sequential biopsies in the recovery-phase for two patients with TTS revealed that membrane expression of GRK2 and β-arrestin2 faded over time. This study provided the first histologic evidence of the involvement of alteration of β-ARs in the development of TTS.